Cytotoxicity of coated and uncoated fibre-reinforced composites. (July 2013) - Frese, Cornelia; Wolff, Diana; Zingler, Sebastian; Krueger, Tanja; Stucke, Kathrin; Lux, Christopher J.; Staehle, Hans Joerg; Erber, Ralf
Abstract Objective. Currently, there are many fibre-reinforced composites (FRCs) available which differ in the type and volume fraction of fibres, pre-treatment of fibres and matrix composition. The aims of this in vitro investigation were to determine whether there is a difference in biocompatibility of FRCs and if coating FRCs with resin composites influences their cytotoxic potential. Materials and methods. Five different FRC materials were tested which were either uncoated or coated with flowable or viscous resin composite. Artificial saliva extracts were prepared according to USP-XXIII and ISO-10993 to determine cytotoxicity by testing cell viability and growth of primary human gingival fibroblasts (HGF) using MTT assay, LIVE/DEAD® assay and cell proliferation assay. The influence of eluates on fibres of the cytoskeleton was investigated by vimentin, tubulin and actinin immunostainings. A two-way ANOVA followed by Scheffe's post-hoc test, which included the factors FRC material and coating procedure, was performed to assess cytotoxicity. Results. All extracts of FRC materials displayed minor cytotoxic potential on HGF cell viability, cell proliferation and integrity of the cytoskeleton. The type of FRC material significantly influenced cell viability (MTT assay) (p < 0.0001), whereas neither the presence of a coating nor the type of coating material resulted in altered cell viability. Distribution and organization of cytosolic fibres was not affected after HGF exposure to eluates. Conclusions. There is a lack of knowledge about the leaching behaviour of commonly available fully pre-impregnated FRCs and their interactions with coating materials. The coating of FRCs with resin composite materials did not impact biocompatibility.